Vaccinated: Marketing Workforce Hybridization - Nadeem, Mohammed (British Journal of Marketing Studies, 2022)
With a hybrid workplace model, employers offer exceptional workplace places, create greater collaboration and community for workers and showcase an example of the modern workplace that is digitally flexible and hybrid.This article aims to explore how the organizations and workers impacted by the long-term impact of the pandemic have accelerated the work-from-home movement and exacerbated organizational issues associated with remote work. This study used qualitative content analysis methods and relied on recent remote work research articles, digital surveys, and interviews. This article provides a viewpoint based on the authors’ professional experiences in academia and the industry. This narrative review aims to underscore how the pandemic brought lasting workforce changes, including the prevalence and permanence of remote and hybrid work. The article aims to present how companies are moving toward a hybrid workforce, capitalizing on both the collaborative nature of in-person work and the flexibility of telecommuting. This research aimed to study the new work models providing opportunities to supercharge customer intimacy, workers’ engagement, and productivity. This study finds that the worker’s challenges regarding job satisfaction, productivity, and organizational commitment work in progress as the COVID-19 pushed organizations into unprecedented and unplanned remote work, and hybrid work is the best remedial approach.The article adds to the body of knowledge regarding remote work in organizations focused on the new hybrid work environment created by the global pandemic. The result of the study recommends that organizations create a level playing field for workers, regardless of their location, empower managers, and care for workers as their highest priority not only structurally but in ways of workspaces, working, and culture for hybrid work. The general discussion includes the conclusions from the study for further qualitative and quantitative investigations with significant implications for academicians, practitioners, and policy makers. Citation: Mohammed Nadeem (2022) Vaccinated: Marketing Workforce Hybridization, British Journal of Marketing Studies, Vol. 10, Issue 3, pp.14-24